Pharmacokinetics study of Pioglitazone (30 mg) tablets in healthy volunteers (Dhaka University Journal of Pharmaceutical Sciences, 2015)
Pioglitazone, an excellent insulin sensitizer, is used for the treatment of type 2 diabetes mellitus (T2DM). The present investigation demonstrated a single dose pharmacokinetic study of pioglitazone tablet in 24 healthy male volunteers in a randomized protocol. Blood samples were collected before and 0.5 to 24.0 h after a single oral dose of a 30 mg pioglitazone tablet. Plasma pioglitazone level was determined using a validated method of reversed phase binary high performance liquid chromatography (HPLC). The pharmacokinetic parameters determined were 1.117 ± 0.315 (?g/ml), 2.5 ± 0.735 (h), 9.014 ± 3.385 (?g.h/ml), 8.081 ± 3.407 (?g. h/ml), 1.315 ± 0.964 (h), 0.707 ± 1.636 (h-1), 0.078 ± 0.02 (h-1) and 8.884 ± 03.808 (h) for Cmax, Tmax, AUC0-?, AUC0-24, Ka, T1/2 (?), Kel, and T1/2(?), respectively. Variation of pioglitazone pharmacokinetic parameters in Bangladeshi population compared to Chinese, Thai and German population may indicate the polymorphic variation in the pioglitazone responsive metabolizing gene CYP3A4 and CYP2C19 in our population. DOI: http://dx.doi.org/10.3329/dujps.v13i2.21896 Dhaka Univ. J. Pharm. Sci. 13(2): 181-186, 2014 (December)